The effects on clinical characteristics, potential factors and outcomes in SAPHO patients during the COVID-19 epidemic - Su, Minhui; Jiang, Haixu; Liu, Shengyan; Shen, Pengfei; Zhou, Dinghua; Zhu, Keqiang; Huang, Zixi; Li, Chen; Li, Meiling (Frontiers in Medicine, 2025)
ObjectivesThe coronavirus disease (COVID-19) pandemic has potentially impacted the care of patients with rheumatic diseases, including Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis (SAPHO) syndrome. We investigates the effects on clinical characteristics, potential factors, and outcomes in SAPHO patients during the COVID-19 pandemic.MethodsSAPHO patients were recruited for this cross-sectional study from Fangshan Hospital of Beijing University of Chinese Medicine. In total, 375 patients (mean age, 47.5 years, 72.53% females) were asked about demographic data, disease status, current treatments, and clinical manifestations during the epidemic, and potential relationships were analyzed.ResultsAmong 375 included patients, 329 were infected with coronavirus 2019. Compared with non-infected patients, infected ones were more likely to have higher disease activity (p = 0.006). However, Janus kinase (JAK) inhibitor use was lower in detected COVID-19 cases than in non-infected cases in our cohort. Disease symptoms during COVID-19 were more commonly present in the non-JAK group than JAK groups, including rhinorrhea (p = 0.030), nasal congestion (p = 0.023), sore throat (p = 0.042), pneumonia (p = 0.044), headache (p = 0.023), and prevalence of palpitation (p = 0.015). In this study, 29 participants underwent tonsillectomy. Tonsillectomized patients showed a significantly higher prevalence of pneumonia than patients who did not undergo tonsillectomy (p = 0.009). The associated effect factors were displayed in the case of previous tonsillectomy using multivariate analysis and Firth’s penalized likelihood. JAK inhibitor use (p = 0.025) and pneumonia (p = 0.011) were more likely to develop in patients with a history of tonsillectomy.ConclusionDisease activity was inversely correlated with JAK inhibitor use in SAPHO patients with COVID-19 during the pandemic. Thus, JAK antagonists have protective effects on SAPHO patients with infections and can significantly mitigate new clinical crown symptoms. However, there was a significant negative correlation between tonsillectomy and the prevalence of SAPHO with COVID-19, which demonstrates that tonsillectomy may be associated with an increased risk of COVID-19 adverse outcomes, especially in cases of taste disorders and pneumonia.